(untitled) (Research, Society and Development, 2022)
Deep digital flexor (DDF) tenotomy and realignment of the distal phalanx (DP) is a therapy used for the treatment of horses with chronic laminitis that, despite the few results described in the literature, presents with promising results. In view of this knowledge gap, this study aimed to describe and compare the clinical and radiographic findings of horses subject to this treatment. To this end, 7 horses with chronic laminitis that underwent tenotomy of the DDF in the metacarpal region and realignment of the DP by means of trimming and shoeing were included in this study. Data were obtained from the moments before and after the procedure. An improvement in clinical and radiographic parameters was observed when comparing the moment before and after the procedure, and it was concluded that this therapy is a viable option for the treatment of horses with chronic laminitis refractory to other therapies.